Stereoselective Peterson Olefinations from Bench‐Stable Reagents and N‐Phenyl Imines. Issue 24 (11th March 2015) - Das, Manas; Manvar, Atul; Jacolot, Maïwenn; Blangetti, Marco; Jones, Roderick C.; O'Shea, Donal F.
Abstract The synthesis of bench‐stable α, α‐bis(trimethylsilyl)toluenes and tris(trimethylsilyl)methane is described and their use in stereoselective Peterson olefinations has been achieved with a wide substrate scope. Product stereoselectivity was poor with carbonyl electrophiles (E/Z ∼1:1 to 4:1) though this was significantly improved by employing the corresponding substituted N‐benzylideneaniline (up to 99:1) as an alternative electrophile. The olefination byproduct was identified as N, N‐bis(trimethylsilyl)aniline and could be easily separated from product by aqueous acid extraction. Evidence for an autocatalytic cycle has been obtained.